Profilometry‐Based Inverse Finite Element Method Indentation Plastometry. Issue 9 (4th August 2021) - Clyne, Trevor William; Campbell, Jimmy Edward; Burley, Max; Dean, James
Abstract : This is a review of the current state‐of‐the‐art regarding a particular approach to extraction of the (quasistatic) stress–strain relationship of a metallic sample from an indentation experiment. It is based on the application of a relatively high load (kN range) to the sample via a large spherical indenter (≈1 mm radius), followed by measurement of the indent profile. This profile is then used as the target outcome for inverse finite element method (FEM) modeling of the test, aimed at converging on the best fit set of parameter values in a constitutive plasticity law (true stress–true strain relationship). This can then be used to simulate any specified loading configuration, including a conventional tensile test. Commercial products are now available in which the indentation, profilometry, and convergence operations are all automated and completed within a few minutes. The review covers the various conceptual and practical issues involved in implementation and optimization of these procedures, including both those related to the measurement system (experimental and FEM simulation) and those associated with the sample (such as anisotropy, inhomogeneities, and residual stresses). An attempt is made to convey an impression of the expected levels of reliability and also the scope for obtaining insights that are not readily obtainable using other types of test. Abstract : This review concerns profilometry‐based indentation plastometry (PIP), which involves iterative finite element method (FEM) modeling of spherical indentation, targeting measured residual profiles. This allows convergence on best fit parameters in a true stress–true strain relationship, leading, in turn, to tensile test characteristics. Automated facilities allow rapid implementation. Various optimization issues are described, as are sample‐related effects, such as those due to anisotropy, inhomogeneities, and residual stresses.